Anette Friis, Danish Agriculture & Food Council, on agriculture in the climate negotiations - CGIAR Research Program on Climate Change, Agriculture and Food Security (2012)
Anette Friis, from the Danish Agriculture and Food Council and coordinator of Farmer's Organisations, talks about the current status of agriculture in the UNFCCC climate change negotiations and the potential outcomes for agriculture at the upcoming climate meeting, COP18, in Doha, Qatar. Anette Friis made a presentation during the 29 Brussels Briefing on climate change, agriculture and food security, organised by the Technical Centre for Agricultural and Rural Cooperation (CTA) and the CGIAR Research Program on Climate Change, Agriculture and Food Security (CCAFS). Here she gives an exclusive interview to CCAFS after the Development Briefing. The Danish Agriculture and Food Council is a valuable partner to CCAFS.